Modelling the Scaling-Up of the Nickel Electroforming Process - Andreou, Eleni; Roy, Sudipta (Frontiers in Chemical Engineering, 2022)
Electroforming is increasingly gaining recognition as a promising and sustainable additive manufacturing process of the “Industry 4.0” era. Numerous important laboratory-scale studies try to shed light onto the pressing question as to which are the best industry approaches to be followed towards the process’s optimisation. One of the most common laboratory-scale apparatus to gather electrochemical data is the rotating disk electrode (RDE). However, for electroforming to be successfully optimised and efficiently applied in industry, systematic scale up studies need to be conducted. Nowadays, well-informed simulations can provide a much-desired insight into the novelties and limits of the process, and therefore, scaling up modelling studies are of essence. Targeted investigations on how the size and geometry of an electroforming reactor can affect the final product could lead to process optimisation through simple modifications of the setup itself, allowing immediate time- and cost-effective adjustments within existing production lines. This means that the accuracy of results that any scaled up model provides, if compared to a successful, smaller scale version of itself, needs to be investigated. In this work a 3-D electrodeposition model of an RDE was used to conduct geometry and model sensitivity studies using a commercial software as is often done in industry. As a next step, a 3-D model of an industrial-scale electroforming reactor, which was 90 times larger in electrolyte volume compared to the RDE, was developed to compare, and identify the key model parameters during scale up. The model results were validated against experimental data collected in the laboratory for both cases to assess model validity.